Analisis Risiko Ergonomi Pada Pekerja Konstruksi CV Ghalea Elka Persada Menggunakan Metode Nordic Body Map (NBM) dan Rapid Entire Body Assessment (REBA) - Ridwan, Khalisa Afifah; Sunaryo, Merry; Ratriwardhani, Ratna Ayu; Luthfiyah, Diana; Akbar, Muhammad Fatih Rizqon (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Construction work is one of the highest-risk sectors for musculoskeletal disorders (MSDs) due to awkward working postures, repetitive tasks, and heavy workloads. This study aims to identify the level of MSD complaints and ergonomic risks among workers in the forklift classroom construction project at CV Ghalea Elka Persada. A quantitative approach was used with a sample of 10 male workers through the Nordic Body Map (NBM) questionnaire and posture analysis using the Rapid Entire Body Assessment (REBA) method. The NBM results showed that 60% of workers were at low risk, 30% at medium risk, and 10% at high risk, with the most common complaints occurring in the lower back (30% very painful) and left upper arm (50% painful). Meanwhile, REBA results indicated that 20% of workers were at very high risk, 50% at high risk, and 30% at medium risk. These findings emphasize the need for ergonomic interventions to prevent further musculoskeletal problems.